Macronutrient content in mangrove sediment at Selangor river, Kg. Kuantan - Zaini, Nurul Nazhifah (2019)
Mangrove forests are a group of trees and shrubs that live in the coastal intertidal zone. The mangrove species grow in saline soil and brackish water. Due to water logged condition in mangrove forest, little free oxygen available. The litter fall and decomposition process make mangrove soil consist of nutrient which is important for mangrove tree such as Nitrogen (N), Phosphorus (P), Potassium (K) and others. Therefore, to know the information on nutrient content in mangrove forest, the study on macro nutrient content was carried out at Sungai Selangor, Kg.Kuantan. The objectives of this study were to determine and compare macronutrient content in Sungai Selangor sediment between plot and different depth. Along the river, five plots were chosen with distance of 50 m between each plot. The sample was collected in five plot and the five plot represent the area of river at Kg. Kuantan. The soil sample were collected using peat auger at different depths. All samples were analyzed using SAS. Based on the finding, the content of Nitrogen (1.36%, ±0.0016) and Potassium ( 27.26,±4.23) were higher in the upper depth (0–15 cm) while the content of Phosphorus (1.21,±0.08) were higher only in lower depth (15–30 cm). In term of plot, Plot 1 contain higher Phosphorus (1.32,±0.15) and Nitrogen (1.37%,±0.0016) but less content of Potassium (22.96,±1.38). The content of Potassium was higher in Plot 3 with value (29.54,±10.79) but low Nitrogen (1.36%,±0.004) and Phosphorus (1.12,±0.08) content compared to other plots.. Therefore, the result obtained show there are different amounts of nutrients of macro nutrients between plot and depth along with it physical and chemical properties.